2018
DOI: 10.1080/2162402x.2018.1440166
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin/IL-8 pathway orchestrates local inflammatory response and tumor invasion by inducing M2 polarization of Tumor-Associated macrophages and epithelial-mesenchymal transition of hepatocellular carcinoma cells

Abstract: We previously demonstrated that neurotensin (NTS) induces local inflammation and promotes tumor invasion in hepatocellular carcinoma (HCC). However, the underlying molecular mechanisms are not clear. In this study, positive correlations between NTS and interleukin (IL)-8 were identified at both the mRNA and protein levels in 71 fresh HCC tissues and 100 paraffin-embedded HCC tissues. Furthermore, significant correlations were determined among the co-expression of NTS and IL-8, infiltration of inflammatory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 52 publications
4
97
0
1
Order By: Relevance
“…NTS has been identified as a local hormone and plays a critical role in the regulation of fat storage, obesity and metabolic disorders. Previous studies also revealed an association of NTS with progression and invasiveness of various cancers, thus is considered to be a potential pharmacological target in cancer therapy [21][22][23][24]. NTS increases cell proliferation by a protein kinase C (PKC)-dependent ligand-induced transactivation of EGFR, which in turn activates the Raf-mitogen-activated protein kinase (MEK)-ERK signaling transduction [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…NTS has been identified as a local hormone and plays a critical role in the regulation of fat storage, obesity and metabolic disorders. Previous studies also revealed an association of NTS with progression and invasiveness of various cancers, thus is considered to be a potential pharmacological target in cancer therapy [21][22][23][24]. NTS increases cell proliferation by a protein kinase C (PKC)-dependent ligand-induced transactivation of EGFR, which in turn activates the Raf-mitogen-activated protein kinase (MEK)-ERK signaling transduction [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is thought to be a driving factor for tumour invasion and progression, regardless of the cause [67,68]. NT has been reported to promote cytokine release, particularly IL-8 via the MAPK and NF-kB pathways, enhancing the migration and invasion capacity of HCC cells [69]. Overexpression of both interleukin-8 and NT in HCC has been associated with portal vein invasion and worse prognosis [69,70].…”
Section: Liver Cancermentioning
confidence: 99%
“…Some cytokines and chemokines play an important role during glioma development and M2 cell polarization. IL‐8 promotes a pro‐oncogenic inflammatory microenvironment by inducing M2‐type tumor‐associated macrophages (TAMs) (Xiao et al, ; Li et al, ). The chemokine MIP‐3α (also called CCL20) could influence tumor growth through mediating macrophage recruitment (Jayaraman et al, ).…”
Section: Introductionmentioning
confidence: 99%